PERBAIKAN PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI (Brassicca juncea L.) YANG DIBERI PUPUK ORGANIK CAIR - Muhamat Ripai; Nurbaiti Nurbaiti; Gunawan Tabrani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This study aims to produce mustard (Brassicca Juncea L) plants with better growth and production by applying liquid organic fertilizer. The research was conduced at the Experimental Garden of the Faculty of Agriculture, Riau University, Pekanbaru. The study was carried out from January to February 2021 in the form of a Completely Randomized Design (CRD) experiment with five treatments with four replications, each treaatment was O1 : Without liquid organic fertilizer, O2 : Dinosaurus 20 ml.1-1 water, O3 : EM4 10 ml.1-1 water, O4 : GDM 20 ml.1-1 water, O5 : Eco Farming 20 ml1-1 water. Parameters observed were plant height (cm), number of leaves (strands), fresh weight per plant (g), fresh Weight per plot (g) and fresh weight per plant fit for consumtion (g). The results of the data were analyzed statistically using variance and followed by Duncan’s multiple distance test at 5% level. The results showed that Eco Farming liquid organic fertilizer 20 ml.1-1 water and GDM 20 ml.1-1 water can improve the growth and production of mustard plants and is the best fertilizers in improving the growth and production of mustard plants. Key words :liquid organic fertilizer, mustard plants, growth and production